Lipoprotein(a) as a novel biomarker for predicting adverse outcomes in ischemic heart failure - Zhang, Biyang; Xu, Yinxiao; Huang, Xin; Sun, Tienan; Ma, Meishi; Chen, Zheng; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2024)
Background: Lipoprotein(a) [Lp(a)] is an independent risk factor for atherosclerotic cardiovascular disease (ASCVD). However, the association between Lp(a) and adverse outcomes in patients with ischemic heart failure (IHF) remains unclear. This study aimed to investigate the relationship between serum Lp(a) levels and the incidence of major adverse cardiovascular events (MACE) in IHF patients. Methods: In this single-center, retrospective cohort study, 1,168 IHF patients who underwent elective percutaneous coronary intervention (PCI) were enrolled. Patients were divided into four groups based on Lp(a) quartiles. The primary endpoint was MACE, defined as a composite of all-cause mortality, non-fatal myocardial infarction (MI), and any revascularization. Cox proportional hazards models were used to evaluate the association between Lp(a) quartiles and adverse outcomes. Restricted cubic spline (RCS) curve were constructed to explore the nonlinear relationship between Lp(a) levels and MACE risk. Subgroup analyses were performed to investigate the association in different subgroups. Results: The incidence of MACE increased significantly across Lp(a) quartiles (Quartile 4 vs Quartile 1: 46.4% vs 22.9%, P<0.001). After adjusting for confounding factors, the highest Lp(a) group remained independently associated with an increased risk of MACE (HR, 95% CI: 2.28, 1.69-3.07, P<0.001, P for trend <0.001), all-cause mortality (HR, 95% CI: 2.33, 1.54-3.54, P<0.001, P for trend = 0.01), and any revascularization (HR, 95% CI: 2.18, 1.35-3.53, P=0.002, P for trend = 0.001). The RCS model demonstrated a nonlinear positive relationship between Lp(a) levels and MACE risk. Subgroup analysis revealed a significant interaction with body mass index (BMI), with a more pronounced association observed in patients with higher BMI (P for interaction < 0.001). Conclusion: Elevated Lp(a) levels were independently associated with an increased risk of MACE, mortality, and revascularization in IHF patients, with a stronger effect in obese individuals.